Evangelical Christianity and Criminal Rehabilitation - Wesley Cohoon (Clinical Sociology Review)
Crime and religion are social constructs that indicate what society considers acceptable and deviant behavior. The connection is further complicated when considering how the formerly incarcerated integrate back into society after incarceration. This article is an engaged scholarship that utilizes clinical sociology to understand the role of religious redemption and criminal rehabilitation. The article specifically utilizes elements of symbolic interactionism to explore how identity, religious conversion, and community impact ex-felons. The author argues that religious redemption is essential for the formerly incarcerated because it allows them to replace their criminal identity with a new one and reinterpret previous mistakes into their life narrative. The article ends with action steps that can be put into practice by religious organizations, nonprofits, and governmental agencies.